Leaf-inspired multiresponsive MXene-based actuator for programmable smart devices - Cai, Guofa (2019)
Natural leaves, with elaborate architectures and functional components, harvest and convert solar energy into chemical fuels that can be converted into energy based on photosynthesis. The energy produced leads to work done that inspired many autonomous systems such as light-triggered motion. On the basis of this nature-inspired phenomenon, we report an unprecedented bilayer-structured actuator based on MXene (Ti3C2Tx)–cellulose composites (MXCC) and polycarbonate membrane, which mimic not only the sophisticated leaf structure but also the energy-harvesting and conversion capabilities. The bilayer actuator features multiresponsiveness, low-power actuation, fast actuation speed, large-shape deformation, programmable adaptability, robust stability, and low-cost facile fabrication, which are highly desirable for modern soft actuator systems. We believe that these adaptive soft systems are attractive in a wide range of revolutionary technologies such as soft robots, smart switch, information encryption, infrared dynamic display, camouflage, and temperature regulation, as well as human-machine interface such as haptics.